Theoretical Study of of Antiferroelectrics and Dielectric Properties of SnCl2·2H2O Crystal - Chandra Upadhyay, Trilok; Sati, Pramod (Asian Journal of Chemistry, 2011)
A two-sublattice pseudospin lattice coupled mode model along with third- and- fourth order phonon anharmonic interaction terms has been considered by using double-time thermal Green's function method for SnCl2·2H2O crystal, expressions for shift, width, renormalized soft mode frequency, Curie temperature, dielectric constant and loss tangent are obtained for tin chloride dihydrate crystal. By fitting model values of physical quantities temperature dependences of soft mode frequency, dielectric constant and loss tangent have been calculated for tin chloride dihydrate crystal. Theoretical results compare well with experimental results of Mognaschi et al.